Inducing The Viability of Deteriorated Jatropha Seeds Through Matriconditioning Technology and Pseudomonas Fluorescens as Biological Agent - Sundahri, Sundahri; Mursyidto, Tofan; Setiawati, Tri C.; Susilo, Hardian A.; Wafa, Ali (Green Publisher Indonesia, 2023)
Jatropha curcas is a prospective vegetable oil or biodiesel and various derivative products as well as phytoremediation (plants cleaning the environment) and phytomining (plants that mine metals such as gold, nickel etc.). However, the commodity often experiences problems in the supply of seeds. The seed used usually has decreased their viability after going through a certain storage period. Therefore, matriconditioning technology and the application of the biological agent Pseudomonas fluorescens were used to increase the viability and vigor of these seeds. The aim of the study was to determine the interaction between the duration of the matrioditioning treatment and the application of Pseudomonas fluorescens to increase the viability and vigor of Jatropha seeds and to determine the optimal duration of the matrioditioning treatment and the dosage of Pseudomonas fluorescens in increasing the viability and growth performance of sprouts and seedlings. Field experiments would be carried out in the greenhouse of the Faculty of Agriculture, Universitas Jember. This experiment was arranged using a factorial design (two factors) with a randomized block design (RBD) repeated 3 times. The result showed that the interaction effect of matriconditioning time and dose of Pseudomonas fluorescens was significantly different on the observed variables of growth speed, vigor index and T50. Combination of 24 hours matriconditioning treatment and dose of Pseudomonas fluorescens 100 ml l-1 produced the best treatment on variables representing seed vigor (growth rate and vigor index).